Efficient Key Management And Authentication Using Enhanced Identity-Based Cryptography For Secure Smart Grid Communications (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The more attacks have been increased over the network and other related system is also being increased for harming the internet and network, the defending system are outdated and outnumbered for protecting the system. The attacks are become dangerous and make more harm to the network or internet. The proposed technique is presenting an enhanced and efficient way within the algorithm of unique cryptography and public key for protecting the network or system and preventing the attacks. The policy and scheme are playing a very important role for making a communication within several clients by using common channel. There are several attacks are existing internally or externally when creating communication over the proposed technique, proposed techniques are completely able to defend or prevent the attacks and reduce the management stress. The accuracy and efficiency are being improved within the proposed technique through the key management policy which has broadcasted the key generation and update the multicast, public and personal key in each node. Proposed system are presenting the polynomial algorithm for reducing the flow of message bulk, Hash-Based algorithm and Cryptographic algorithm for processing over the high speed data processing